2019
DOI: 10.1159/000495939
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Serotonin 2C Receptors with SB-242084 Moderates Reduced Locomotor Activity and Rearing by Cannabinoid 1 Receptor Antagonist AM-251

Abstract: The endocannabinoid and serotonin (5-HT) systems have key roles in the regulation of several physiological functions such as motor activity and food intake but also in the development of psychiatric disorders. Here we tested the hypothesis, whether blockade of serotonin 2C (5-HT2C) receptors prevents the reduced locomotor activity and other behavioral effects caused by a cannabinoid 1 (CB1) receptor antagonist. As a pretreatment, we administered SB-242084 (1 mg/kg, ip.), a 5-HT2C Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…The distance travelled by mice from all tested groups was comparable to the one covered by the vehicle-treated animals. Though altered motility of rodents can be expected after administration of cannabinoids [24,25], our outcomes were in line with results published by Kruk-Słomka and colleagues [10].…”
Section: Discussionsupporting
confidence: 92%
“…The distance travelled by mice from all tested groups was comparable to the one covered by the vehicle-treated animals. Though altered motility of rodents can be expected after administration of cannabinoids [24,25], our outcomes were in line with results published by Kruk-Słomka and colleagues [10].…”
Section: Discussionsupporting
confidence: 92%
“…As mentioned above the inverse agonist Rimonabant, found to be effective for weight-loss and smoking cessation, was quickly withdrawn following the emergence of severe psychiatric side effects. 182 In line with this, CB1 inverse agonist, AM251 has been found to reduce social interactions in rodents 183,184 and nonhuman primates. 115 Interestingly and in contrast to CB1 inverse agonists, two preclinical studies found that administration of a CB1 neutral antagonist, AM4113, did not produce anxiogenic or depressive side effects when administered in rats.…”
Section: Summary Of Current Drugs Targeting the Endocannabinoid Systemmentioning
confidence: 62%
“…1, Table 1), a receptor known to be involved in the neurobiology of anxiety (Petrie et al, 2021). In a broader sense, CB 1 R antagonism has been shown to reduce locomotor, exploratory, and rearing activity (Bogathy et al, 2019). Further studies using tests more sensitive to anxiety-related behaviors are needed.…”
Section: Behavior Effectsmentioning
confidence: 99%